Improved fluorescent Listeria spp. biosensors for analysis of antimicrobials by flow cytometry. Issue 4 (30th June 2022) - Reich, Sebastian J.; Stohr, Jonas; Goldbeck, Oliver; Fendrich, Bastian; Crauwels, Peter; Riedel, Christian U.
Abstract: The global increase in antibiotic resistance of pathogenic microorganisms requires the identification and characterization of novel antimicrobials. Bacterial biosensors expressing fluorescent proteins such as pHluorin variants are suitable for high‐throughput screenings. Here, we present Listeria spp. pH‐sensitive biosensors with improved fluorescence for single‐cell analysis of antimicrobials by flow cytometry. Abstract : For screening of novel antimicrobial compounds, we developed improved Listeria spp. biosensor strains. By using pH‐dependent fluorescence, a quick readout of the integrity status of the cell is possible. We further demonstrate the assessment of cell integrity of the sensor bacteria on the single‐cell level by flow cytometry.